Analysis of Financing Schemes From Land Value in Transit Oriented Development at Bubulak Terminal - Alvian, Novan (Universitas Ibn Khaldun Bogor, 2023)
Oriented areas are often known as Transit Oriented Development (TOD) requiring financing, which is absolutely necessaryto accommodate developing activities and encouraging regional growth and land use plans in accordance with TOD regulations,Bubulak Terminal is one of the terminals in Bogor City because has a variety of economic activities be it bus companies (PO), public transport, trade and services. This study plans land use in accordance with PermenATR/KaBPN No. 16 of 2017 concerning TOD Development Guidelines and using a financing scheme for the Bubulak Terminal Area using analysis calculations with the Financial and Economic Calculation Methods, the results of these calculations that are in accordance with data from internet literature studies of scientific papers and books. The results of the analysis of the TOD area of Bubulak Terminal with a mix use designation of 1606 pcu/hour. The results of the calculation of the Financial Calculation value of NPV (Net Present Value) are RP 38.144.000.000,00 and the results of the IRR calculation for the Bubulak Terminal area show an IRR value of 14.92 %, so the project is feasible to run/choose with a capital cost (WACC) of 11.56%. While the calculation result of the Economic Net Present Value (ENPV), the calculation result is RP 325.848.272.000,00 and the result of the Economic internal rate of return (EIRR) is 31.19%, the project will benefit and is feasible to run with revenue in 2023 Stakeholders involved in the TOD area at Bubulak Terminal, namely BPTJ as the regulator as well as the Responsible Agency for Cooperation Projects (PJPK) in developing TOD in Jabodetabek.